Dynamic Openness and Finance in Africa - Simplice Asongu; Jules R. Minkoua N. (African Governance and Development Institute (AGDI), 2017)
This study assesses dynamics of openness and finance in Africa by integrating financial development dynamics of depth, activity and size in the assessment of how financial, trade, institutional, political and other openness policies (of second generation structural and institutional reforms) have affected financial development. The empirical evidence is based on Generalized Method of Moments with data from 28 African countries for the period 1996-2010. The following findings are established. (i) While the de jure (KAOPEN) indicator of financial openness improves financial depth, the de facto (FDI) measurement decreases it, with the effect of the latter measure positive on financial size. (ii) Whereas trade openness improves financial depth, its effect on financial activity and size is negative. (iii) Institutional openness has a positive effect on financial dynamics of depth and activity, while its effect on financial size is negative. (iv) Political openness and economic freedom are detrimental to financial depth and activity. Justifications for these nexuses are discussed.
Keywords: E50; G20; O16; O17; O55; 330; Banking; Trade; Institutions; Politics; Africa